FILOSOFI DAN NILAI BUDAYA DALAM ARSITEKTUR RUMAH ADAT SUKU KABOLA (BANG TOWO) - Maria Bainhana; Halena Muna Bekata, Mahalita S. Moban, Margerita A. Mapada, Lutgardis S. Maure, Lodia M. Kamengko, L (CV. ADIBA AISHA AMIRA, 2025)
This study aims to determine the philosophy and cultural values in the architecture of Bang Towo traditional house in Kabola tribe in Alor, East Nusa Tenggara. This research uses qualitative methods. Data analysis techniques are carried out by reducing data, presenting data and drawing conclusions. This research was conducted in Kopidil Village, Kabola District. The informant in this research is the Chief of Adat in Kabola Tribe. The results showed that: Bang Towo Traditional House was established in 2013-2014 and inaugurated in 2015. Bang Towo Traditional House consists of two words, namely the word ‘Bang’ which means village and the word ‘Towo’ which means three. So the word Bang Towo itself means three villages (Uang, Wabuli, Alibang, where the Bang Towo Traditional House is the traditional house of the three villages in Kopidil. Bangtowo not only functions as a place to live but also as a symbol of cultural identity and local wisdom of the Kabola community. This research explores the philosophical meaning behind architectural elements, as well as room patterns that reflect values of togetherness, ancestral beliefs, and harmonious relationships with nature. By understanding this philosophy, this research emphasises the importance of preserving traditional houses as cultural heritage that represents local identity and contains educational and spiritual values that are relevant for today.